2018
DOI: 10.1016/j.chb.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

I “like” the way you look: How appearance-focused and overall Facebook use contribute to adolescents' self-sexualization

Abstract: I "like" the way you look: How appearance-focused and overall Facebook use contribute to adolescents' self-sexualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 81 publications
2
27
0
1
Order By: Relevance
“…Although these platforms are designed to stimulate positive feedback from peers (Valkenburg, Peter, & Schouten, 2006), negative feedback, which often targets users' appearance (CSM, 2015), also occurs. Appearance feedback may increase one's belief that he or she is exclusively valued because of his or her sexual attractiveness, which can induce objectification processes (Trekels, Ward, & Eggermont, 2018).…”
Section: Sexualizing Online Media Use During Adolescencementioning
confidence: 99%
“…Although these platforms are designed to stimulate positive feedback from peers (Valkenburg, Peter, & Schouten, 2006), negative feedback, which often targets users' appearance (CSM, 2015), also occurs. Appearance feedback may increase one's belief that he or she is exclusively valued because of his or her sexual attractiveness, which can induce objectification processes (Trekels, Ward, & Eggermont, 2018).…”
Section: Sexualizing Online Media Use During Adolescencementioning
confidence: 99%
“…The dark side of social mediaand Fifty Shades of Grey introduction to the special issue: the dark side of social media The massive-scale diffusion of social media in private life as well as workplaces calls for increased awareness and understanding of its risks and adverse consequences for individuals, organizations and societies (Garcia and Sikström, 2014;Fox and Moreland, 2015;Mäntymäki and Islam, 2016;Oberst et al, 2017;Trekels et al, 2018). For example, the recent discussion on the role of social media in amplifying socially undesirable phenomena such as fake news (Allcott and Gentzkow, 2017) and hate speech (Farkas et al, Forthcoming) demonstrates a clear need for a critical analysis of the undesirable societal consequences of social media.…”
mentioning
confidence: 99%
“…Moreover, research has shown that the majority of youths’ Facebook network consists of peers known from the offline world (Manago, Taylor, and Greenfield 2012). As such, boys’ comparison with idealized profile pictures on Facebook may increase their perception that the muscular ideal is attainable and inspire them to engage in self-sexualizing practices (Ho, Lee, and Liao 2016; Trekels, Ward, and Eggermont 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our measure of self-sexualizing behavior included items assessing clothing behaviors centered on the chest, leaving out investment of other body areas or grooming, as well as appearance changing behaviors that may also be sexualizing. Future studies should include a wider range of self-sexualizing behaviors when examining how boys’ media exposure contribute to their self-sexualization (e.g., Trekels, Ward, and Eggermont 2018).…”
Section: Discussionmentioning
confidence: 99%